Pengaruh Dimensi Kualitas Pelayanan dan Harga Terhadap Keputusan Pembelian Jasa di PT. Paham Potensi Niaga - Ahmad Mara Sampurna; Nurhayani Nurhayani; Yoga Adiyanto (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This research aims to determine the influence of service quality and price on purchasing decisions at PT. Paham Potensi Niaga. This research is a replication study using a quantitative approach method. The population of this study was 185 people, samples were taken using purposive sampling with a sample size of 65 employees. Data was obtained from the results of distributing questionnaires to respondents. This research analysis uses multiple linear regression analysis with the results of the analysis showing that service quality and price influence purchasing decisions as proven by the t test which shows tcount > ttable. The results of the f test analysis show that service quality and price simultaneously influence purchasing decisions. This can be proven from the results of the f test by paying attention to the value of Fcount > Ftable. And the significance value is <0.05. The concentration of this research is on purchasing decisions which are influenced by service quality and price. Suggestions for further research are expected to be able to retest based on dimensions and indicators other than those examined in this research